2019
DOI: 10.4067/s0717-95022019000401429
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Characteristics and Physical Performance of Young Elite Kosovo Soccer Players

Abstract: The aim of this study was to establish the anthropometric and physical profiles of young soccer players according to their playing position and to determine their relevance for competition success. One hundred and twenty young soccer players participated in the study. Players aged 19 were classified into the following groups: defenders (n=40), midfielders (n=40) and attackers (n=40). The anthropometric variables of participants (height, weight, body mass index, 4 skinfold, 2 diameters, and 2 perimeters) were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
9
0
4
Order By: Relevance
“…In another study conducted by Sylejmani et al (Sylejmani et al, 2019) with 120 young Kosovar elite football players, it was reported that the Yo-Yo Endurance Test results of midfielders were statistically significantly higher (p <0.05) compared to other positions. In our study, parallel to Sylejmani and his friends' finding, it was determined that central midfielders have higher MAS parameters compared to other positions, and particularly this difference is statistically significant compared to wingers (p <0.05).…”
Section: Discussionmentioning
confidence: 88%
“…In another study conducted by Sylejmani et al (Sylejmani et al, 2019) with 120 young Kosovar elite football players, it was reported that the Yo-Yo Endurance Test results of midfielders were statistically significantly higher (p <0.05) compared to other positions. In our study, parallel to Sylejmani and his friends' finding, it was determined that central midfielders have higher MAS parameters compared to other positions, and particularly this difference is statistically significant compared to wingers (p <0.05).…”
Section: Discussionmentioning
confidence: 88%
“…Freely available online -OPEN ACCESS Nutrition for Physical Activity and Sports patear al arco 41 . Esto se contrapone con lo informado en futbolistas jóvenes de elite 42 , donde MC consiguen desempeños más bajos respecto a DF y DL. Las discrepancias podrían ser consecuencia de las características de los futbolistas, la frecuencia y tiempo de entrenamiento que influirían en su desempeño físico 17 .…”
Section: Discussionunclassified
“…We analyzed the locomotor performance of young (U15-U19) soccer players over 6 weeks during training sessions, as well as the relationship between locomotor performance and the mechanical load and motoric tests. The analytical examination of body parameters and physical test results took place according to international practice (Sylejmani et al, 2019). The movement and motoric tests showed the key parameters of the players' performance during matches (Rampinini et al, 2007).…”
Section: Discussionmentioning
confidence: 99%